Management of mangrove landscape and ecosystem for ecotourism - H.T. Silalahi; M. Basyuni; E.Y. Aritonang; B. Slamet; K.S. Hartini; A. Wee (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Mangroves have high potential for advancing ecotourism because of their position at the intersection of land and sea. Many studies have reported that mangroves and coastal environments are the right places for the development of sustainable ecotourism. Ecotourism aims to preserve natural environments, playing a crucial role in conservation efforts and serving as a unique type of tourism experience. The aim of this study is to assess the tourism prospects of significant mangrove ecosystems in Sumatra, Indonesia, and to identify suitable approaches for fostering ecotourism. The implementation of ecotourism can serve as a means to safeguard the ecosystem while also influencing the socio-economic conditions of the local community.METHODS: The research was conducted in Beras Basah Village, located in the Pangkalan Susu District of Langkat Regency, North Sumatra, Indonesia. It commenced in November 2023 with the initiation of the Beras Basah ecotourism project and concluded in January 2024. The research commenced by introducing the ecotourism landscape through the utilization of a geographic information system. Subsequently, questionnaires and discussion group forums were employed to analyze the community, visitors, and relevant stakeholders. Furthermore, an assessment of the potential mangrove ecosystem was conducted, encompassing transects, ecological suitability, and carrying capacity. Lastly, a comprehensive analysis of the research findings was performed, focusing on the strengths, weaknesses, opportunities, and threats associated with the study.FINDINGS: The potential area for ecotourism covers ​​38 hectares with various well-designed facilities and infrastructures. The mangroves were utilized as a source of sustenance with the overall condition of community. This study obtained 8 species of mangroves consisting of Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba, Avicennia marina, Bruguiera gymnorrhiza, Xylocarpus granatum, and Scyphiphora hydrophyllacea. The species of fauna observed were two species of birds (Haliaetus leucogaster, Bubulcus ibis), three species of reptiles (Varanus salvator, Fordonia leucobalia, Mabouia multifasciata), three types of mammals (Macaca fascicularis, Tupaia glis, Martes flavigula), seven types of fish (Plotosus canius, Epinephelus lanceolatus, Ophiocara porocephala, Lutjanus argentimaculatus, Lates calcarifer, Scatophagus argus, Mugil cephalus), five types of mollusks (Cerithidea cingulata, Telescopium telescopium, Cerithidea quadrata, Murex trapa, Polymesoda bengalensis), and four types of crustaceans (Scylla serrata, Metapograpsus sp., Panaeus monodon, Panaeus merguensis). The two studied stations exhibited varying levels of ecological suitability. One approach to protection is the enforcement of a visitor quota based on the carrying capacity of the areas, was 86 individuals per day. Furthermore, the analysis of strengths, weaknesses, opportunities, and threats revealed that the improvement of mangrove ecosystem management, the addition of supporting facilities, and the provision of environmental and conservation education to tourists can contribute to the enhancement of ecotourism.CONCLUSION: Ecotourism plays a crucial role in preserving the sustainability of the mangrove ecosystem while also influencing socio-economic factors. Through thorough study and analysis of both human behavior and natural processes, effective management strategies can be developed to support ecotourism initiatives. This investigation has the potential to support the preservation of the mangrove ecosystem in Beras Basah District through the introduction of landscape management strategies for the advancement of ecotourism. The findings of this study highlight the significance of ecotourism and emphasize the importance of expanding ecotourism initiatives, enhancing infrastructure, and promoting environmental awareness.